2020
DOI: 10.1101/2020.10.09.328609
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Face neurons in human visual cortex

Abstract: The exquisite capacity of primates to detect and recognize faces is crucial for social interactions. Although disentangling the neural basis of human face recognition remains a key goal in neuroscience, direct evidence at the single-neuron level is virtually nonexistent. We recorded from face-selective neurons in human visual cortex, in a region characterized by functional magnetic resonance imaging (fMRI) activations for faces compared to objects (i.e. the occipital face area, OFA). The majority of visually r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 58 publications
(73 reference statements)
0
2
0
Order By: Relevance
“…Second, we predominantly studied multi- and single-unit spiking activity, whereas semantic information may be more relevantly encoded at the population level. Studies have generally found the same category selectivity in face patches using noninvasive imaging, single-unit activity, or multiunit activity ( 8 , 29 ), but detailed tuning patterns likely differ, as they do even among face neurons. Thus, it is conceivable that single neurons may respond to face-related features at the same time that population activity encodes semantic categories ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, we predominantly studied multi- and single-unit spiking activity, whereas semantic information may be more relevantly encoded at the population level. Studies have generally found the same category selectivity in face patches using noninvasive imaging, single-unit activity, or multiunit activity ( 8 , 29 ), but detailed tuning patterns likely differ, as they do even among face neurons. Thus, it is conceivable that single neurons may respond to face-related features at the same time that population activity encodes semantic categories ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Face-selective neural signals have also been found in humans by intracranial field potential recordings ( 6 ); subsequently, by noninvasive measurements (e.g., ref. 7 ); and recently, with unit recordings ( 8 ).…”
mentioning
confidence: 99%